Modification of anti-cancer co-crystal for thymidylate synthase inhibition: Molecular dynamics study - Sabri, Nadia Hanim; Halim, Siti Nadiah Abdul; Zain, Sharifuddin Md; Lee, Vannajan Sanghiran (Faculty of Science, Chiang Mai University, 2018)
Raltitrexed (tomudex) is an alternative antifolate drug to 5-fluorouracil (5-FU) to inhibit thymidylate synthase (TS) by decreasing dihydrofolate reductase (DHFR) activity. The clinical trial shows the potential of raltitrexed towards TS inhibition can be enhanced by combining the raltiterexed with other anticancer agents. This present work discovered the combination of raltitrexed with modifying 5-FU based co-crystal (compound 1) have high effectiveness with manageable toxicity via computational approach. The X-ray structure of human TS (1HVY) was retrieved from Protein Database Bank. The molecular docking of protein-ligand complexes has been performed to investigate the potential of ligands as TS inhibitor by disrupting both promising binding sites; nucleotide and folate. The best-ranked conformations were further explored via parameterized molecular dynamic simulation. The simulated result by molecular dynamic simulation suggested that the modified co-crystal (compound 1) enhancing binding strength of raltitrexed to inhibit TS with binding free energy (-45.68 kcal/mol) compared to raltitrexed alone (-16.57 kcal/mol). Per-residue decomposition revealed that the Arg50A, Leu192A, Cys195A, His196A, Asn226 and Gly217A are the pivotal residues that playing main role in the nucleotide binding site. The binding free energy in the folate binding site is majority come from the interaction with Phe80A, Ile108A, Trp109A, Asp218A, Phe225A, Tyr258A, Met311A and Ala312A residues.